Diversity of Agarics in Achanakmar – Amarkantak biosphere reserve, Chattisgarh - Shukla, R V; tripathi, Arpita Mani; Shukla, Kamlesh K; Tiwari, Mahesh K (Mushroom Research, 2015)
Please see the full text